Perlindungan Hukum Bagi Saksi yang Memberikan Fakta dalam Perkara Pidana - Mutia Febriana; Arrum Budi Leksono (Syntax Literate, 2023)
This study aims to obtain information and analyze the law regarding legal protection for witnesses based on Law no. 31 of 2014 concerning Amendments to Law no. 13 of 2006 concerning the Protection of Witnesses and Victims. By using the approach method in this research is a normative juridical approach. The Witness and Victim Protection Agency (LPSK) is considered important, because the wider community views that it is time for witnesses and victims to be given protection in the justice system. The role of witnesses and victims in every trial of criminal cases is very important because often witness statements can influence and determine the tendency of judges' decisions. As an institution that was born with the main task of providing protection for witnesses and victims, LPSK has shown a track record, which, although still small, has been praised by various parties. Several protections are carried out for witnesses and victims in serious cases, from which protection then contributes to upholding the law in order to achieve justice. Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, in Article 1 point 3 states that: “Victims are people who suffer physical, mental and/or economic losses caused by a criminal act. Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, in Article 1 point 3 states that: "Victims are people who suffer physical, mental and/or economic losses caused by a criminal act.